2013
DOI: 10.3329/bja.v10i2.17322
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Arrangement of Structures at Hilum of Human Kidney

Abstract: Context: There is a variation in the arrangement of structures at hilum which may create problem for the surgeon during dissection of hilum of kidney. Moreover, developmental anomalies like, constriction at pelviureteric region, double renal pelvis, accessory renal arteries etc are not uncommon. So, adequate anatomical knowledge of kidney specially at hilum is required for successful surgery of this reason. Objective: To study the variation in the arrangement of renal vessels and renal pelvis at hilum. Study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…Similar observation was also made by Samprio et al [19] during their various studies where they found that in majority of cases a branch of renal artery or a tributary of renal vein lies in close proximity of pelvis implying prehilar branching pattern of renal artery. Hassan et al [20] in 2012 studied the variation in arrangement of structures at renal hilum in Bangladesh population and observed that renal pelvis was the posterior most structure in 100% kidneys which is in disagreement with our observations.…”
Section: Discussioncontrasting
confidence: 77%
“…Similar observation was also made by Samprio et al [19] during their various studies where they found that in majority of cases a branch of renal artery or a tributary of renal vein lies in close proximity of pelvis implying prehilar branching pattern of renal artery. Hassan et al [20] in 2012 studied the variation in arrangement of structures at renal hilum in Bangladesh population and observed that renal pelvis was the posterior most structure in 100% kidneys which is in disagreement with our observations.…”
Section: Discussioncontrasting
confidence: 77%
“…Knowledge of renal hilar structures variations is useful for operating surgeons to identify and individually clamp the hilar structures, which is advantageous over en-bloc clamping. Knowledge of branching pattern of the renal artery is very important for the proper analysis of radiographic interpretation of renal vasculature and for planning surgical procedures in cases of renal trauma, renal transplantation, and partial nephrectomy [18].The variations in the branching patterns of the renal vessels are critical issues and a challenging task for a radiologists who interpret renal angiograms and for the urologists who perform laparoscopies [19]. Several studies have reported that anomalous courses of the renal vessels which had crossed the renal pelvis, caused ureteropelvic obstructions [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…In 66.3%, the kidney's pelvis was the posterior-most structure. However, a study done in the Bangladesh population noted renal pelvis is the posterior-most structure in 100% of the kidneys [ 22 ]. Before performing various procedures, urologists need to have a thorough understanding of the arrangement of the renal hilar structures, as they will be performing hilar dissection and hilar vascular clamping [ 10 ].…”
Section: Discussionmentioning
confidence: 99%